Measurements of the Radioactive Iodide and Pertechnetate Uptake for the Study of the Trapping and Binding Functions of the Human Thyroid - Koutras, D. A.; Sfontouris, J.; Pandos, P. G.; Chryssikou, M.; Gatsios, D. M.; Malamos, B. (Nuklearmedizin - NuclearMedicine, 1972)
The uptake of 131I and 99mTc by the thyroid, 5, 30 and 60 min after i.v. administration was measured in 18 normal persons, 45 patients with simple goitre and 39 patients with Graves disease. The 5 min 99mTc uptake was higher than the 131I ohne, but at 30 min and at 60 min the 131I uptake was usually higher than that of the 99mTc. There was a considerable overlap of all these parameters especiallv between Graves disease and simple goitre, but a better diagnostic separation of the thyrotoxic patients was achieved by the 60 min 131I uptake than by the other measurements. The ratio of the 131I/99mTc uptakes was higher in the thyrotoxics than in the patients with simple goitre. This difference at 30 and 60 min was statistically significant even if only the goitrous patients with a high 99mTc uptake were considered. Since 131I is bound organically in the thyroid to a much greater degree than 99mTc, these findings suggest that in many cases of non-toxic goitre, although the trapping function may be increased as much as in thyrotoxicosis, the binding capacity of the gland is not proportionally increased. This hypothesis was also supported by the fact that following administration of Carbimazole, a drug which inhibits organic binding, the 30 and 60 min 131I uptake and the 131I/99mTc ratio were reduced in the patients with Graves disease, but there was no significant effect on those with simple goitre. This supports the conclusion that the thyroidal organic binding of iodide may be impaired in some patients with simple goitre. It is also concluded that early 99mTc uptake measurements have not a greater diagnostic value than the conventional 131I tests, and so their use as a routine procedure is not recommended.